PENGUATAN SISTEM PENGAWASAN KEIMIGRASIAN UNTUK PEMBERANTASAN TPPO: ANALISIS YURIDIS DAN SINERGI ANTAR LEMBAGA - Waskito, Sarwo; Saputra, Rio; Darmawan, Didit; Fajarudin, Mochamad; Junaidi, Junaidi (Gapenas Publisher, 2025)
Human trafficking is a traditional crime that poses a serious threat to human rights and national security. In Indonesia, the complexity of TPPO requires a strategic role from the Directorate General of Immigration as the frontline agency, particularly in controlling travel documents, monitoring border crossings, and preventing the exploitation of migrant workers. Through a literature review using a normative legal approach, this study analyzes the effectiveness of the role, legal basis, and forms of cooperation between Immigration and related institutions. Various regulations, such as Law No. 6/2011 on Immigration, Law No. 21 of 2007 on the Eradication of TPPO, and other implementing regulations, form a strong foundation for preventive and repressive actions against TPPO. The importance of cross-sectoral collaboration, improving technology-based surveillance systems, and public education for optimal prevention is also emphasized. The study's findings indicate the need to strengthen inter-agency synergy, improve regulations, and update surveillance systems to support the comprehensive eradication of human trafficking.